Prognostic Risk Factors of 30-Day Death in Traumatic Lower Limb Fracture Patients with Acute Pulmonary Embolism: A Single-Center Retrospective Study - Huanhuan Li; Yijun Yu; Yuting Wang; Qian Zhang; Ye Gu (Canadian Respiratory Journal)
Background. To explore the prognostic risk factors of 30-day death in patients with traumatic lower limb fracture (TLLF) complicated with acute pulmonary embolism (APE). Methods. 295 consecutive TLLF patients diagnosed as APE according to pulmonary artery CT angiography, hospitalized in our hospital from January 2017 to December 2021, were included in this study. Patients were divided into nonsurvival group and survival group according to 30-day follow-up results. After adjusting age, sex, and all the clinical variables with P values of <0.2 with backward stepwise method (likelihood ratio), multivariate Cox regression analysis was used to analyze risk factors of 30 days all-cause death in TLLF patients with APE. The area under curve (AUC) calculated by receiver operating characteristic curve (ROC) and the incremental model were used to determine the prognostic potential of identified risk factors. Results. 29 patients died during 30-day follow-up. Simplified pulmonary embolism severity index (sPESI) score ≥1 (P<0.05), Wells score ≥7 (P<0.01), and pulmonary hypertension (P<0.01) were associated with higher risk, while anticoagulant therapy (P<0.01) was associated with lower risk of all-cause death during 30 days follow-up in APE patients. Compared with sPESI score, Wells score plus pulmonary hypertension produced better predictive efficacy. Prognostic value of sPESI score could be enhanced by adding Wells score, pulmonary hypertension, and anticoagulant therapy to the predicting models. Conclusions. Wells score ≥7 and pulmonary hypertension are independent predictive risk factors of 30-day all-cause death in TLLF patients with APE.